Modelling of fracture in pressure vessels by thin shell isogeometric analysis. Issue 2 (6th August 2021) - Singla, Rijul; Anitescu, Cosmin; Singh, Sunil K.; Singh, Indra V.; Mishra, Bhanu K.; Rabczuk, Timon; Zhuang, Xiaoying
We aim to model fracture on pressure vessel surfaces so that its rupture can be avoided. It is well known that pressure vessels have wide-spread applications in almost all industries. They are often subjected to high pressures and extreme temperatures and in some typical applications they even carry highly flammable or hazardous substances. In the presence of cracks, the state of stress near the fracture zone becomes very high, due to the phenomenon of stress singularity at the crack tips. This greatly reduces the strength of the material and can lead to early failure. In this paper, the geometry of pressure vessels is discretised using splines which are used as the basis for isogeometric analysis (IGA). Initially, the stress analysis of thin pressure vessel is carried out in the absence of cracks by implementing IGA-based Kirchhoff-Love shell theory, and the results are compared with analytical or standard available solutions. The crack is assumed to cross the entire thickness and is introduced either in axial or circumferential direction.